(untitled) (Polish Yearbook of International Law, 2023)
This article examines the role of environmental human rights and the rights of nature in the era of the Anthropocene. The research question is whether the concept of the Anthropocene itself is a constructive remedy for the ecological destruction. The United Nations General Assembly resolution acknowledging a universal human right to clean environment is a ground-breaking event in a long process of the creation of such a right. This article examines the status quo of this right at present, both generally and in regional human rights treaties, as well as in the relevant case law and literature. The rights of nature are also examined, as they have become a very topical issue in light of the recent decision of the Conference of the Parties of the Convention on Biological Diversity, which expressly grants such a right. The question which may be posed is whether the approach adopted by the Anthropocene – which treats all actors equally – reflects the reality. The Western (Global North) approaches to the destruction of the Earth are contested by the Global South. The fractured approaches (by both the Global South and the Global North) to the decline of the environment may render questionable the suitability of the Anthropocene paradigm.